2021
DOI: 10.3389/fpsyg.2021.770579
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Demographics, Language Learning Experience, and Cognitive Control to Chinese Reading Comprehension

Abstract: The study investigates whether learners’ demographics (e.g., age, education, and intelligence-IQ), language learning experience, and cognitive control predict Chinese (L2) reading comprehension in young adults. Thirty-four international students who studied mandarin Chinese in mainland China (10 females, 24 males) from Bangladesh, Burundi, Congo, Madagascar, Nigeria, Rwanda, South Africa, and Zimbabwe were tested on a series of measures including demographic questionnaires, IQ test, two cognitive control tasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…The study found that the learners in the experimental group showed a significant improvement in their retention of English collocations compared to the control group. Xie et al (2021) investigate the impact of storytelling on vocabulary acquisition among young EFL learners in China. The participants were 60 children aged 8-10 years old, who were divided into two groups: an experimental group and a control group.…”
Section: Storytelling Promotes Comprehension and Retention By Providi...mentioning
confidence: 99%
“…The study found that the learners in the experimental group showed a significant improvement in their retention of English collocations compared to the control group. Xie et al (2021) investigate the impact of storytelling on vocabulary acquisition among young EFL learners in China. The participants were 60 children aged 8-10 years old, who were divided into two groups: an experimental group and a control group.…”
Section: Storytelling Promotes Comprehension and Retention By Providi...mentioning
confidence: 99%
“…Comparable issues regarding reading comprehension and intervention was addressed by several authors (Azizi et al, 2020;Johnston et al, 2008;Khonamri et al, 2020;Wu et al, 2020;Xie et al, 2021), who in their research tried to point out the differentiating in understanding while referring to cognitive models of comprehension. Another research by Capellini, Pinto, Cunha (2015) focused on teachers, while their goal was to examine the efficiency of intervention program focused on the reading comprehension.…”
Section: Introductionmentioning
confidence: 99%